Protein and energy levels to pigs from 10 to 25 kg live weight - Barbosa, Hacy Pinto; Costa, Waldomiro; Fialho, Elias Tadeu; Gomes, Paulo Cezar (Pesquisa Agropecuaria Brasileira, 2014)
One hundred and twelve Landrace piglets (56 castrate males and 56 females) with aproximately 40 days of age were used to analyse their response to different protein and energy levels. A factorial experiment 2 x 2 was designed, corresponding to the treatments A (3.300 kcal of ED/kg and 20% of crude protein), B (3.300 kcal of ED/kg and 18% of crude protein, C (3.500 kcal of ED/kg of crude protein), and D (3.500 kcal of ED/kg an 18% of crude protein). Animals were fed ad libitum and their performance was measured from 10 to 25 kg live weight. Differences among treatments were not significant for average daily gain (0.519; 0.492; 0.494 and 0.473 kg) and feed efficiency (1 .90; 2.02; 1.87 and 1.96 for treatment A, B, C and D, respectively). Interactions between protein and energy levels were not observed. Feed efficiency of the pigs fed with 20% protein in level (1.89), independently from the energy level studied, was significantly(P<0.05) better than the one obtained by the pigs ted with 18% protein level (1.99).